Analisis Penerapan Program PKBL Berdasarkan Prinsip Umum Corporate Social Responsibility (CSR): Studi Kasus pada PT Waskita Karya - Panggabean, Rosinta Ria; Pratiwi, Ratih Nugrahati (Binus Business Review, 2011)
This research aims to analyse whether the implementation of PKBL program at PT Waskita Karya comply with general principles of CSR and Peraturan Menteri Negara BUMN No. PER-05/MBU/2007, and to know whether the implementation report of PKBL at PT Waskita Karya comply with those principles. The method used in this research is descriptive method with content analysis approach by analysing the implementation and reporting of social responsibility,. The results of this research show that PT Waskita Karya is already has done its PKBL. But the implementation did not comply with GRI Guidelines and PKBL Report is not a Social Responsibility Report mentioned in UU No. 40 Tahun 2007. The recommendations are PT Waskita Karya should fill its Working and Budget Plan in compliance with Permen BUMN No. PER-05/MBU/2007, do more various events on its Program Bina Lingkungan and learn more CSR issues in GRI Guidelines so that Program Bina Lingkungan PT Waskita Karya could be equal with CSR.